2022
DOI: 10.5005/ijcdas-56-2-75
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Control of Bronchial Asthma in Children Using Childhood Asthma Control Test

Abstract: Background. The use of Childhood Asthma Control Test (C-ACT) has been advised for monitoring asthma control by the Global Initiative for Asthma (GINA) guidelines.Objective. To validate the tool C-ACT for the assessment of control of asthma and to examine the correlation between C-ACT score and lung function assessed by forced expiratory volume in one second (FEV 1 ).Methods. This was a prospective observational study conducted between January 2010 to January 2011. Children diagnosed to have bronchial asthma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In addition to the original study by Liu et al 11 13 other studies identified a recommended cut‐off for uncontrolled asthma, ranging from ≤18 to ≤24 19,20,23,25–29,35,36,38,39,41 . Of these 13 studies, three recommended the original cut‐off of ≤19, 26,27,38 eight recommended a cut‐off higher than the original, 19,23,25,28,35,36,39,41 and two recommended a lower cut‐off of ≤18 20,29 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the original study by Liu et al 11 13 other studies identified a recommended cut‐off for uncontrolled asthma, ranging from ≤18 to ≤24 19,20,23,25–29,35,36,38,39,41 . Of these 13 studies, three recommended the original cut‐off of ≤19, 26,27,38 eight recommended a cut‐off higher than the original, 19,23,25,28,35,36,39,41 and two recommended a lower cut‐off of ≤18 20,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Gender of the study participants ranged from 47% to 72% male, and participants ranged from 4 to 14.2 years old. Three studies included children outside of the C‐ACT's intended age range of 4–11, instead including ages 5–14, 27 4–12, 28 and 4–14.2 29…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations